Molecular Spectrum, Ethnic and Geographical Distribution of Thalassemia in the Southern Area of Hainan, China - Yu, Ying; Lu, Chunjiao; Gao, Ying; Li, Cuiyun; Li, Dongxue; Wang, Jie; Wei, Hui; Lu, Zhaohui; You, Guoling (Frontiers in Pediatrics, 2022)
Background: Thalassemia is one of the most common genetic diseases in southern China. Accurate population frequency data regarding the occurrence and distribution of thalassemia are important for designing appropriate prevention strategies for thalassemia. This study aims to reveal the molecular spectrum, ethnic and geographical distribution of thalassemia in the southern area of Hainan Province, China. Methods: A total of 9813 suspected carriers of thalassemia were screened for genetic analysis by using the PCR-reverse dot blot hybridization method targeting three known deletions of α-thalassemias (--SEA, -α3.7, and -α4.2), three nondeletional mutations of α-thalassaemias (αCS, αQS, and αWS) and the 17 most common mutations of β-thalassaemias in the Chinese population. Results: Approximately 6924 subjects were genetically diagnosed as thalassemia carriers or patients, including 5812 cases of α-thalassemia (83.9%), 369 cases of β-thalassemia (5.3%), and 743 cases of α-composite β-thalassemia (10.7%). A total of 21 distinct genotypes were identified among the 5812 α‐thalassemia carriers, -α4.2/αα, -α3.7/αα, and -α3.7/-α4.2 were the most common α-thalassemia genotypes. The most frequent β-thalassemia genotype was βCD41–42/βN, with a notable proportion of 69.6%, followed by the β-28M/βN, βIVS-II-654/βN, βCD71–72/βN, βE/βN, and βCD17/βN genotypes. In addition, 37 genotypes were detected among the 743 cases of both α- and β-thalassemia mutations. The α-thalassemia genotypes were most commonly found in the Li people, who accounted for 73.5% of α-thalassemia carriers. The β-thalassemia genotypes were most commonly identified in the Han people, who accounted for 59.4% of β-thalassemia carriers. Among the subjects carrying both α- and β‐thalassemia variations, only three ethnic minorities were identified, including the Li, Han, and Miao people, accounting for 82.0%, 17.4%, and 0.7%, respectively. Conclusions: Our study indicates that there is high genetic heterogeneity, geographical and ethnic differences in thalassemia in populations in the southern area of Hainan Province. These findings will be helpful in guiding genetic counseling and prenatal diagnosis of thalassemia in Hainan Province.